A feminilidade nas organizações na visão de homossexuais masculinos: entre a dominação masculina e o estigma - Moura, Renan Gomes de (2017)
Organizations act as "agents" of conduct and normalizing in your most seek to strengthen conventional genre standards, aiming to reproduce the image of the central role of man as the great provider and valuing the figure of the "male" applying all their efforts for the sake of business. Bourdieu (1984) reports that every society creates mechanisms for the broader relations of domination to win autonomy and characterized as natural and unquestioned, denominated thus "masking of symbolic capital". The relationship of domination not only social practices because traverses such practices and reaches the field of consciousness and interfere until the Constitution of identities. In a historical context "the feminine has been built as subordinate to men, who favored the men a prestige, privilege and power" (SANTANA, 2010, p. 75). This work possessed as ultimate goal to understand the stigma of femininity inside of organizations, from the perspective of the gay guy and your connection with the male domination. The selection of subjects of research was done by the reference, i.e. a subject of research indicates other. For this methodological technique used for recruitment of subjects of research was the snowball. The method used for the production of the corpus of research was the method of individual interviews in depth and the method of analysis of the corpus of research was based on critical discourse analysis (ACD). It was observed in this work that stigma of femininity within organizations is understood by subject gay through features that aim to disqualify and subdue the femininity in both gay and effeminate woman, because they believe that organizations are environments that prevail the heterormatividade and the power of the straight man.